Про один тип освітлювальних приладів на прикладі досліджень в урочищі Гончарі-Кожум’яки - Сушко, А.О. (Археологія і давня історія України, 2022)
Стаття присвячена комплексному аналізу та
характеристиці колекції модерних керамічних освітлювальних приладів яка сформована в ході археологічних досліджень в урочищі Гончарі-Кожум’яки та знаходяться на збережені в фондах Музею історії
міста Києва. Проведено морфологічний, технологічний та функціональний аналіз колекції. На основі якого вдалося виділити чотири основних типи засобів для освітлення. Встановлено, що вироби у
формі мисочок з отворами або прорізом в гнізді універсальні, могли використовуватися і як свічники
і як світильники. Освітлювальні прилади з суцільним гніздом використовувалися лише як свічники,
а вироби без гнізда, скоріше за все — виключно як
олійні світильники. Вироби виготовлялися місцевими гончарями та належать до продукції серійного виробництва. Таким чином, введено до наукового обігу дані, які вперше формують комплексне
уявлення про склад, типові риси та особливості
колекції керамічних освітлювальних приладів, які
були виявлені під час археологічних досліджень на
території гончарної слободи міста Києва та знаходяться на збережені в міському музеї. The paper is devoted to the complex analysis and
characteristics of the collection of modern ceramic
lighting from the excavation in Honchari-Kozhumyaki
region of Kyiv and is kept in the storage of the Museum
of History of Kyiv. The processed collection consists of
620 units of lighting of various degrees of preservation
and 262 fragments.
Morphological, technological and functional analysis
of the collection was performed. Based on which we
managed to distinguish four main types of lighting:
with a slot on one side, with several holes in the bottom
of the socket, with solid sockets for candles without any
additional details and products without a socket. In addition
to structural details, the shape of the product
and methods of forming the crown were taken into account,
which made it possible to distinguish several
modifications within each type.
Bowl-shaped items with holes or a slot in the nest
are universal, and could be used as candlesticks and
lamps. That is both candles and liquid fuel could be
used as fuel. Lighting with a solid socket were used
only as candlesticks, and items without a socket, most
likely, exclusively as oil lamps.
The characteristics of manufacturing technology
and the process of organization of production is made.
It was ascertained that the lighting were made by local
potters and belong to the series production. Manufactured
in standard form using the scheme of machine
design.
Thus, the data, introduced into scientific circulation,
for the first time form a comprehensive view of the composition,
typical features and features of the collection
of ceramic lighting, discovered during archaeological
research in the pottery settlement of Kyiv and stored
in the city museum.